The Difference of Bax Protein Expression between Endometrioma and Ovarian Carcinoma - Chandran Frinaldo Saragih; Riza Rivany; Mohamad Fauzie Sahil; Fadjrir Fadjrir; Edy Ardiansyah; Muhammad Rizki Yaznil; Munauwarus Sarirah (Molecular and Cellular Biomedical Sciences, 2019)
Background: Endometriosis is a benign disease that has malignant properties such as genetic polymorphism, loss control of cell proliferation, infiltration, and local spread or to distant places. Several endometriosis studies linking endometrioma/ ovarian endometriosis with an increased risk of ovarian malignancy give rise to a transformation phenomenon of endometriotic cysts into malignancy. Bax is a pro apoptotic protein whose expression decreases in a malignancy. This decrease is related to the poor prognosis of endometrioma and ovarian carcinoma. This study was aimed to identify the expression and the difference of Bax expression between endometrioma and ovarian carcinoma.Materials and Methods: Fifty of paraffin blocks of endometrioma tissue and ovarian carcinoma (serous, mucinous, clear cell, and endometrioid type) were examined by immunohistochemical using Bondmax Full Automatic with specific monoclonal antibody to identify Bax expression. The difference of Bax expression score between endometrioma tissue and ovarian carcinoma was tested by Mann-Whitney test with significant value was set at p<0.05.Results: This study found that mean Bax expression score in endometrioma tissue and ovarian carcinoma was 3.88 and 3.72. No difference of Bax expression between endometrioma tissue and ovarian carcinoma (p>0.05). No difference of Bax expression between the clinical stages and histopathological types of ovarian carcinoma (p>0.05).Conclusion: There are no statistically significant difference in Bax protein expression in ovarian cancer and endometrioma.Keywords: Bax expression, endometrioma, ovarian carcinoma, apoptotic resistance